Non-enzymatic hydrolysis of fluorescein diacetate (FDA) in a Mediterranean oak (Quercus ilex L.) litter (European Journal of Soil Science, 2008)
We show the presence of interfering substances when the total microbial activity in litter samples is measured with fluorescein diacetate (FDA), and we propose some methodological modifications to avoid such interference. Three distinct litter layers (the OhLn, the OhLv and the OhLf) of evergreen oak (Quercus ilex L.) were characterized by 13C CPMAS NMR and the spectra show that the recalcitrant aromatic and phenolic compounds increase with the degree of degradation of litter. A wide range of sources of interference in the hydrolysis of FDA was found. To understand the origin of this interference, sterilized litter materials (i.e. γ-irradiated or autoclaved) and a wide range of organic substances (i.e. amino acids, glucose, sorbitol and organic humic acids) were investigated. Insignificant differences on the FDA hydrolysis activity (FDA activity) were found in the γ-irradiated and non-irradiated OhLn litter, indicating that γ-irradiation does not destroy enzymes. Conversely, after heat-sterilization of litter, samples showed FDA activity corresponding to 60, 34.8 and 30.8% (in the OhLn, the OhLv and the OhLf layers, respectively) of that of control litters. This indicates the presence of non-enzymatic interfering substances in the FDA assays. As the humification and litter depth increased, hydrolysis of FDA due to interferences decreased, indicating degradation and/or chelation of interfering substances. We hypothesize that lysine, arginine, histidine and cysteine are mainly responsible for the hydrolysis of FDA. We suggest that the use of phosphate buffer (50 mm, pH 7.0) with incubation < 30 minutes, in combination with a temperature between 30 and 40°C, produces insignificant interference in the determination of the final FDA activity in litter samples.

Annual dynamics of phosphatase activities in an evergreen oak litter: influence of biotic and abiotic factors (Soil Biology and Biochemistry, 2004)
As part of a study of the processes involved in litter biodegradation, we considered the variations over 1 year of the phosphatase activities in sclerophyllous evergreen oak litter (Quercus ilex L.). Evergreen oak is representative of tree species in the forests of the French Mediterranean area. Acid (E.C. 3.1.3.2.) and alkaline (E.C. 3.1.3.1.) phosphatases, were measured over 13 months in the forest litter, along with several biotic and abiotic variables, potentially involved in the regulation of these enzymes. These comprised moisture, temperature, pH, water-extractable inorganic P (PI ), fungi, culturable heterotrophic bacteria and protein concentrations. Moisture considerably affected the production of proteins and acid phosphatases, probably formed by litter microorganisms. This result corroborated the study of Criquet et al. [Soil Biology and Biochemistry 34 (2002) 1111] which indicated that rainfall was the most important factor regulating the production and the activity of numerous enzymes in sclerophyllous forest litter. However, it appeared that moisture cannot alone predict all of the variations in phosphatase activities and the mineralisation rate of organic P (PO). Indeed, principal component analyses (PCA) and multiple regressions showed that temperature and bacterial communities were also implicated in phosphatase dynamics and PO mineralisation. Acid phosphatases were negatively correlated with the temperature, whilst alkaline phosphatases were positively correlated with this variable. The signiﬁcant correlation obtained between bacteria and PI concentrations, and the lack of correlation between bacteria and both acid and alkaline phosphomonoesterases, suggest that other important phosphatase types, such as phosphodiesterases, must be strongly implicated in PO mineralisation of the litter and in the regulation of P microbial metabolism.

Endoglucanase and β-glycosidase activities in an evergreen oak litter: annual variation and regulating factors (Soil Biology and Biochemistry, 2002)
This paper represents the third part of a larger study about the processes involved in litter biodegradation in an oak copse in France. It concerns the variations in activities of endoglucanases and of β-glycosidases over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Q. ilex is the most abundant tree species in forests of the French Mediterranean area. The activities of several endoglucanases and β-glycosidases, and the concentrations of the proteins and reducing sugars were measured in the evergreen oak litter between October 1997 and October 1998. Several biotic and abiotic factors, potentially involved in the regulation of the activities of these hydrolyzing enzymes, were also measured: culturable heterotrophic bacteria, cellulolytic bacteria and cellulolytic fungi, moisture, temperature and pH of the litter. Under this Mediterranean climate, the moisture of the litter was strongly correlated with many factors and is likely to be important in regulating the temporal dynamics of various biological parameters. A multiple regression analysis showed that the annual dynamic of the culturable heterotrophic bacteria was primarily influenced by moisture but also by variations in concentration of reducing sugars in the litter. Moreover, these bacteria were correlated with the activities of several β-glycosidases, and specifically with the N-acetyl-glucosaminidases (r=0.93). No relationships were established between the number of cellulolytic microorganisms (bacteria and fungi) and the activities of endoglucanases (i.e. cellulases and hemicellulases). The seasonal trends of certain biotic processes, and the influence of pH and of temperature on these processes are also discussed. Electrophoretic analyses were used to estimate the number of cellulase and xylanase isoenzymes in the litter, and to study their fluctuations over one year. The prevailing cellulase isoenzyme had a Rf of 0.64, and there was no relationship between the abundance of cellulolytic microorganisms and the electrophoretic profiles of the cellulases. In the case of the xylanases, the electrophoretic profiles were homogenous throughout the year, and the prevailing xylanase had a Rf of 0.75.

Purification of a new isoform of laccase from a Marasmius quercophilus strain isolated from a cork oak litter (Quercus suber L.) (MYCOLOGIA, 2002)
A new isoform of laccase from Marasmius quercophilus is described in this study. The strain of this white-rot fungus was isolated for the first time on a cork oak litter. This isoform exhibited certain common properties of laccases (a molecular weight of 65 Kda, an optimum pH of 6.2 with syringaldazine). But this laccase has also particularly novel features: the best activity measured was observed at high temperatures (80 C) and this isoform was not inhibited with EDTA. Furthermore, this induced laccase was able to transform most of the aromatic compounds tested without the addition of mediators to the reaction mixture, and the transformation of certain chlorophenols (2-chlorophenol and 2,4-dichlorophenol) by a laccase isoform from M. quercophilus is reported here for the first time. We also demonstrate the importance of 2,2'-azinobis(3-ethylbenzthiazoline-6-sulfonate) (ABTS) as a mediator since it allowed veratryl alcohol and p-hydroxybenzoic acid transformation. Moreover, new products of transformation were observed using the combination of ABTS with this isoform of laccase.

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter

Laccase activity of forest litter (Soil Biology and Biochemistry, 1999)
Laccases are blue-copper enzymatic proteins involved in the transformation of polyphenolic compounds, such as lignin, into forest litter. A method to measure their activity was developed using an evergreen oak litter as a model system. We considered factors that aect the extraction of these enzymes and the measurement of their activity. The factors studied included powdering of the leaves, adding polyvinylpolypyrrolidone or Tween 80, adsorption of enzymes on centrifugation pellets, concentration of the extracts, nature and molarity of the extraction solvent, amount of powdered leaves used for enzymatic extraction, extraction time, pH, and temperature during the measurement of the activity